A South African perspective: Do excise duties imposed on tobacco products drive the illicit trade in tobacco products? - Matlala, Tshegofatso (Department of Finance and Tax, 2024)
The use of tobacco products is said to be the second leading cause of preventable deaths and disability in the world, accounting for approximately eight million deaths around the world annually, with about one million deaths as a result of exposure to secondhand smoke. South Africa and many other countries have recognized the need for tobacco control measures and have adopted strategies and policies to combat the use of tobacco products. According to the World Health Organization (WHO), the imposition of excise duties on tobacco products is considered one of the most effective tobacco control measures. South Africa imposes an excise duty on tobacco products that are intended to be consumed within South Africa. The South African Government has been consistently increasing excise duties on tobacco products from the early 1900s. The consistent increase in the excise duties on tobacco products over the years has resulted in a significant decrease in the consumption of cigarettes in South Africa. From as far back as 1997, the tobacco industry in South Africa has argued against the increase of excise duties on tobacco products, claiming that it would result in an increase in the illicit trade in tobacco products. The illicit trade in tobacco products is on the rise and the tobacco industry has attributed this increase to the continual increase of excise duties on tobacco products. In this regard, the tobacco industry made a submission to the Standing Committee on Finance wherein it requested that the South African government cease the increase of excise duties for a period of three years in order to address the issue of illicit trade. The purpose of this dissertation is to consider whether the claims made by the tobacco industry are true and to consider what drives the illicit trade in tobacco products in South Africa. To this end, an analysis of the way in which tobacco products are taxed; the characteristics and consequences of the illicit trade in tobacco products; and the drivers of the illicit trade in tobacco products was performed. The experience of Brazil and Georgia were considered alongside the WHO Framework Convention on Tobacco Control (WHO FCTC). Article 6 of the WHO FCTC provides price and tax measures which are to be implemented to reduce the demand for tobacco products, while Article 15 provides measures to address the illicit trade in tobacco products. This dissertation finds that the illicit trade in tobacco products is not solely driven by tax and price differential, but by a combination of varying factors including weak tax administration, weak border control, corruption, as well as tax and price differentials. More specifically from a South African perspective, this dissertation finds that the growth in the illicit trade in tobacco products in recent years has been as a result of weak administration and the disbanding of the High-Risk Investigation Unit (HRIU) in 2014.